2021
DOI: 10.1186/s12969-021-00510-8
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with IL-1 blockade in systemic juvenile idiopathic arthritis – data from the German AID-registry

Abstract: Background Systemic juvenile idiopathic arthritis (sJIA) is a complex disease with dysregulation of the innate immune system driven by cytokines. A major role is ascribed to interleukin-1β (IL-1β), supporting the autoinflammatory character of the disease and offering an effective blocking mechanism for treatment. Here we present clinical practice data from the German AID-registry for patients treated with IL-1 inhibition (IL-1i). Methods In 2009 a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
4
6
0
Order By: Relevance
“…Noteworthy, despite IL-1 inhibition has been supposed to be less suitable in patients with a prominent joint involvement ( 18 , 19 , 28 , 29 ), articular items have proved to be responsive in the overall group, disregarding the type of disease course. Looking at literature, polyarticular involvement was observed to be a negative predictor for clinical response to IL-1 inhibition, especially when considering the persistence of arthritis ( 19 , 28 ). Actually, the presence of polyarthritis could be associated to a loss of systemic inflammatory activity in favor of an autoimmune phenotype ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, despite IL-1 inhibition has been supposed to be less suitable in patients with a prominent joint involvement ( 18 , 19 , 28 , 29 ), articular items have proved to be responsive in the overall group, disregarding the type of disease course. Looking at literature, polyarticular involvement was observed to be a negative predictor for clinical response to IL-1 inhibition, especially when considering the persistence of arthritis ( 19 , 28 ). Actually, the presence of polyarthritis could be associated to a loss of systemic inflammatory activity in favor of an autoimmune phenotype ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical response to biological medication was maintained in most patients (ANA 54/80, CANA 20/27). The study acknowledged positive clinical results with both IL-1 inhibitors (anakinra and canakinumab), which were well-tolerated by patients and showed reasonable safety and efficiency when tested in a true clinical framework [ 81 ].…”
Section: Biomarkers For Diagnosis Treatment and Disease Activity In S...mentioning
confidence: 99%
“…In recent decades, special efforts have been made to establish complex consensus-based plans for the early diagnosis and management of sJIA as an autoinflammatory disease. These strategies also involve the implementation of expensive treatment methods that directly target the main initiating and supporting cytokines (i.e., IL-1 and IL-6) of the chronic inflammatory process [ 81 , 87 ].…”
Section: Biomarkers For Diagnosis Treatment and Disease Activity In S...mentioning
confidence: 99%
“…Whereas, IL-1 and IL-17 act synergistically to cause cartilage destruction in JIA. Furthermore, it is reported that IL-1 and TNF-α together enhance the IL-23-mediated production of IL-17, and both IL -1 and IL-23 act in harmony to enhance the T helper-(Th-)17 response [4], [6]. Further, recent studies have reported the role of IL-17 in initiating both joint inflammation and cartilage destruction in JIA [7].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly elevated levels in the blood and synovia of patients just before the fever spikes contribute to the disease's clinical course. Therefore, the recent advanced strategies to manage JIA include IL-1 and IL-6-directed therapies [6].…”
Section: Introductionmentioning
confidence: 99%